The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s13024-022-00516-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective reduction of astrocyte apoE3 and apoE4 strongly reduces Aβ accumulation and plaque-related pathology in a mouse model of amyloidosis

Abstract: Background One of the key pathological hallmarks of Alzheimer disease (AD) is the accumulation of the amyloid-β (Aβ) peptide into amyloid plaques. The apolipoprotein E (APOE) gene is the strongest genetic risk factor for late-onset AD and has been shown to influence the accumulation of Aβ in the brain in an isoform-dependent manner. ApoE can be produced by different cell types in the brain, with astrocytes being the largest producer of apoE, although reactive microglia also express high levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 100 publications
(88 reference statements)
0
27
0
Order By: Relevance
“…10g, h), suggesting an inability to transition from DAM towards HLA, and therefore to a full response to Ab plaques. Despite APOE4 being the major genetic risk factor for AD, our data suggest that its cell-autonomous role in microglia is rather limited, probably reflecting the fact that it operates across multiple cell types as recently shown for example for astrocytes and microglia 35,36 . As shown above, the main effect of ApoE knock out models on microglia responses seems non-cell autonomous via the decreased accumulation of amyloid-b plaques.…”
Section: Alzheimer's Disease Risk Genes Modulate Human Microglial Cel...mentioning
confidence: 53%
“…10g, h), suggesting an inability to transition from DAM towards HLA, and therefore to a full response to Ab plaques. Despite APOE4 being the major genetic risk factor for AD, our data suggest that its cell-autonomous role in microglia is rather limited, probably reflecting the fact that it operates across multiple cell types as recently shown for example for astrocytes and microglia 35,36 . As shown above, the main effect of ApoE knock out models on microglia responses seems non-cell autonomous via the decreased accumulation of amyloid-b plaques.…”
Section: Alzheimer's Disease Risk Genes Modulate Human Microglial Cel...mentioning
confidence: 53%
“…In the AD mouse model, removing APOE ε4 reduced microglial activation and alleviated Aβ deposition in the cortex (Mahan et al, 2022). Interestingly, knocking out APOE ε4 in microglia did not affect Aβ plaque or transcriptional expression compared to controls (Henningfield et al, 2022), indicating that other glial cells, such as astrocytes, play essential roles in Aβ production and accumulation, while microglia appears to maintain Aβ homeostasis.…”
Section: Apolipoprotein E and Astrocytesmentioning
confidence: 96%
“…RNA-Sqe analysis showed that induced pluripotent stem cells carrying the APOE4 allele express lower levels of genes related to lymphatic markers, implying APOE4 might play a key role in meningeal lymphosclerosis (e.g., the premature shrinkage of mLVs) and then result in impaired meningeal lymphatic clearance [ 54 ]. The finding that selective reduction of astrocytic APOE4 strongly protected against tau-mediated and A-β-accumulated neurodegeneration also indirectly supported this evidence [ 55 , 56 ]. Taking into account these evidences, we proposed a new insight that APOE4-induced cholesterol dysregulation may herald a novel mechanism of CSVD by regulating the dysfunction of the glymphatic-mLVs system.…”
Section: The Underlying Role Of the Glymphatic And Meningeal Lymphati...mentioning
confidence: 85%